Thyroid Storm Masked by Hemodialysis and Glucocorticoid Therapy in a Patient with Rheumatoid Arthritis - Sasaki, Yohei (S. Karger AG, 2012)
Thyroid function test values are generally at low levels in patients with end-stage kidney disease. Life-threatening thyrotoxicosis or thyroid storm is rare, especially in hemodialysis (HD) patients, and is characterized by multisystem involvement and a high mortality rate if not immediately recognized and treated. Here, we report a female patient with severe symptomatic thyroid storm, receiving long-term HD and glucocorticoid therapy. Methimazole at a dose of 15 mg per day, β-adrenergic blockade and HD succeeded in controlling the patient's condition by gradually adjusting the target dry weight for hyperthyroidism-induced weight loss. When she was discharged from the hospital, her dry weight was reduced from 47.2 to 39.2 kg. The management of patients with severe symptomatic thyroid storm on HD represents a rare scenario. It is essential to initiate the available treatments as early as possible to reduce its mortality.